Maternidade compartilhada e crianças encarceradas: etnografando o dia de domingo em um presídio - Ferreira, Núbia Guedes de Barros (2020)
The present work, extracted from the ethnographic research carried out in in a female prison located in a large northeastern city, in a research with children and on maternity, aims to observe the social interaction between the children and their imprisoned mothers, but also with the other social actors that they met in that prison unit on the family's visiting day, Sunday. The anthropological research was carried out with women who are serving time or awaiting trial in a closed regime. Therefore, the presence of children and their families is intertwined with the type of women's prison regime. The work discussed the perceived gifts, the feelings extracted from the prison, bodies that speak, that are silent, but that communicate. The methodological resources used in the research were direct observation, informal conversations, drawing, field notebook and memorization. Children, who emerge from research, emerge as social actors. In the field, forms of conception of the prison were revealed, such as: the one elaborated by the institution, the one invented by the children's families, above all, by the maternal grandmothers for the young children, but also, I presented the perception of the big children. I observed some signs of resistance in the prison, a way of reinventing family life, such as sheets that lined the floor of the visiting area. In them, aspects of home, sacredness, territoriality were observed, which re signified that hostile space. I presented the magazine of children's bodies, the punishments of mothers who reflect on children for being without the right to visit. Emerged from the research, shared motherhood, matrifocality, the form of care for the new generations of that group. Finally, Sunday is the day of a great meeting, a way of resisting the mortification of the self caused by the prison system, a day of celebration, a day of family fraternization, it is a day of the family, it is a way for those couples to re socialize, unconsciously if they reinvent themselves despite the obliteration of their identities, especially that of the mother. Prison chaos erupted, “doing nothing” as ways of intensifying the reprimand. The great meeting carried out during the visit was observed as the great and only form of resocialization of the sentence found in that prison, carried out by those displaced families who, unconsciously, humanize the sentence, evoking the state's duty of resocialization